2005
DOI: 10.1121/1.1840531
|View full text |Cite
|
Sign up to set email alerts
|

Lip kinematics in long and short stop and fricative consonants

Abstract: This paper examines lip and jaw kinematics in the production of labial stop and fricative consonants where the duration of the oral closure/constriction is varied for linguistic purposes. The subjects were speakers of Japanese and Swedish, two languages that have a contrast between short and long consonants. Lip and jaw movements were recorded using a magnetometer system. Based on earlier work showing that the lips are moving at a high velocity at the oral closure, it was hypothesized that speakers could contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 27 publications
(43 reference statements)
5
29
1
Order By: Relevance
“…In the case of a long consonant, the syllable final component is lax. This is in accordance with the idea of virtual target (Löfqvist & Gracco, 1997;Löfqvist, 2005) suggesting that the position of the virtual target for the lips is varied in order to control the duration of closure/constriction, meaning higher target and bigger amplitude for long consonants. Since displacement is claimed to strongly correlate with velocity, long consonants should also have higher peak velocity.…”
Section: Previous Articulatory Studies Of Estoniansupporting
confidence: 58%
See 2 more Smart Citations
“…In the case of a long consonant, the syllable final component is lax. This is in accordance with the idea of virtual target (Löfqvist & Gracco, 1997;Löfqvist, 2005) suggesting that the position of the virtual target for the lips is varied in order to control the duration of closure/constriction, meaning higher target and bigger amplitude for long consonants. Since displacement is claimed to strongly correlate with velocity, long consonants should also have higher peak velocity.…”
Section: Previous Articulatory Studies Of Estoniansupporting
confidence: 58%
“…Velocity profiles of relevant articulators exhibit more varied patterns regarding the quantity contrast. Several researchers have reported lower articulatory velocity for long segments than for short ones (e.g., Smith, 1995 andLöfqvist, 2005 for Japanese stops, sonorants, and fricatives; Šimko et al, 2014 for Finnish stop consonants), but others have found significantly higher velocity for geminates than singletons (Löfqvist, 2005 for Swedish and Bouarourou et al, 2008 for Tarifit Berber stops and fricatives). In addition, no significant effect of quantity on movement velocity was reported in several other studies (e.g., Fivela et al, 2007 for Italian stops and sonorants and Zeroual et al, 2008 for Moroccan Arabic stops).…”
Section: Articulation Of Geminatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be expected that geminates would have longer formant transitions than singletons, reflecting a lower velocity of articulator movement (and lower gestural stiffness) in producing the geminate, as found in articulatory studies by Smith (1995) and Löfqvist (2005Löfqvist ( , 2007 for Japanese. Myers & Hansen (2005) found that long vowels have longer formant transitions than short vowels in Finnish, and it would be reasonable to expect a similar difference between long and short consonants.…”
Section: Effects Of Consonant Lengthmentioning
confidence: 99%
“…In many languages, the acoustic analysis shows that the ratio geminate/non geminate phoneme duration varies from one language to another: higher in Arabic (Obrecht, 1965;Zeroual et al, 2008), Japanese (Lahiri, Hankamer, 1988) and Italian (Stevens, Hajek, 2004), but lower in Swedish (Löfqvist, 2005). Furthermore, the intervocalic geminate plosives are usually produced with a very long closure, which constitutes their major acoustic and perceptive cue (Obrecht, 1965;Lahiri, Hankamer, 1988;Zeroual et al, 2008).…”
Section: Introductionmentioning
confidence: 99%